7(x+5)=6(x-6)+x

Simple and best practice solution for 7(x+5)=6(x-6)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+5)=6(x-6)+x equation:


Simplifying
7(x + 5) = 6(x + -6) + x

Reorder the terms:
7(5 + x) = 6(x + -6) + x
(5 * 7 + x * 7) = 6(x + -6) + x
(35 + 7x) = 6(x + -6) + x

Reorder the terms:
35 + 7x = 6(-6 + x) + x
35 + 7x = (-6 * 6 + x * 6) + x
35 + 7x = (-36 + 6x) + x

Combine like terms: 6x + x = 7x
35 + 7x = -36 + 7x

Add '-7x' to each side of the equation.
35 + 7x + -7x = -36 + 7x + -7x

Combine like terms: 7x + -7x = 0
35 + 0 = -36 + 7x + -7x
35 = -36 + 7x + -7x

Combine like terms: 7x + -7x = 0
35 = -36 + 0
35 = -36

Solving
35 = -36

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x-5=-6x+14 | | 3x-5=-6+14 | | 6y+9+9y= | | 9f+9f=2 | | 4.5(7.6z+3)-3= | | lnx+x=5 | | 5x^2+6x+13=0 | | 9y-11=-10x+5 | | 7.6(4.5z-3)+3= | | y+8=7x | | ln(m)=.5(ln(x^2-y)) | | x/2-29=22 | | -5(-3)(-7)(-1)= | | 7(x+3)+2=7x+9 | | 3x^2/3x | | 0.18(2x)=29.5 | | 8x+10y=170 | | 0.18(2x)=59 | | y-15x=3 | | -17.3-m=22.8 | | 5+30=x+6 | | 2xy+10=90 | | x^9=-7 | | 3x+39=0 | | 3i*3i= | | -0.9(7.5w-6)-9= | | i*3i= | | 9(x-4)+x=10(x-4)+4 | | .02=15.4 | | -5x+3.6=2.1-4x | | 7.5(-0.9w-9)-6= | | x^2+2=3y |

Equations solver categories